2004
DOI: 10.3748/wjg.v10.i22.3345
|View full text |Cite
|
Sign up to set email alerts
|

Patients with brain metastases from gastrointestinal tract cancer treated with whole brain radiation therapy: Prognostic factors and survival

Abstract: Brain metastases occur late in the course of gastrointestinal tumors. Pretherapeutic variables like KPS and the number of brain metastases have a profound influence on treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 40 publications
3
64
0
1
Order By: Relevance
“…19 York et al 18 observed a greater incidence of primary tumors in the proximal stomach (67%) among patients with brain metastases. Similarly, Bartelt et al 5 also reported that 50% of gastric cancer patients who developed brain metastases had primary tumors in the gastric cardia. Concurrent systemic metastases were present in all patients with gastric cancer brain metastases and most commonly involved the bone (46%), liver (42%), and lung (29%).…”
Section: Gastric Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…19 York et al 18 observed a greater incidence of primary tumors in the proximal stomach (67%) among patients with brain metastases. Similarly, Bartelt et al 5 also reported that 50% of gastric cancer patients who developed brain metastases had primary tumors in the gastric cardia. Concurrent systemic metastases were present in all patients with gastric cancer brain metastases and most commonly involved the bone (46%), liver (42%), and lung (29%).…”
Section: Gastric Cancermentioning
confidence: 99%
“…45 For CRC, the bDFI ranges from 22.6 to 27.6 months (Table 5), which is considerably longer than for other GI cancers (range, 5.6-30 months) 5,46 and lung cancer (average 4 months) but shorter than breast cancer (average 3 years). 45 Hammoud et al 45 investigated factors affecting bDFI for CRC and identified Dukes' stage and treatment status of extracerebral metastatic disease.…”
Section: Colorectal Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…However, BM from esophageal carcinoma (BMEC) is extremely rare. According to Bartelt and colleagues, the incidence of BM from gastrointestinal tumors, including esophageal, gastric, and colorectal carcinomas, is less than 4% [4] . As the incidence of esophageal cancer has been reported to have gradually increased in the United States [5] , the number of reports on BMEC has also increased in recent years [6] .…”
mentioning
confidence: 99%